Analysis of trends in ecology factor influencing the macro, meso and microlevels’ systems competitiveness formation - T.V. Averihina (Marketing i Menedžment Innovacij, 2016)
The aim of this article. Analysis of trends in ecology factor influencing the macro, meso and microlevels’ systems competitiveness formation Results of the analysis. Trends in the macroeconomic level: as we observe from the correlation analysis’ results for the studied countries, their development reveals a strong statistical association between the global competitiveness index and indicators of the main competitiveness factors. In particular, the correlation coefficients of the global competitiveness index and human development index, GDP per capita, economic transformation and economic freedoms are 0,913; 0,784; 0,917 and 0,830 respectively. These estimates do highlight the fact that the environmental factor (ecological transformation index) reveals, along with indexes and indicators of social and economic development, strong statistic relationship with index of global competitiveness. Trends in the meso-economic level: to analyse relationship between environmental factors and competitiveness at the meso-economic (regional) systems level, we did estimate the region competitiveness based on the competitive advantage indices using the latest techniques of competitive comparisons. To be noted is that the correlation analysis of the statistical relationship between partial indices of competitive advantages and the integral index of region’s competitiveness, calculated using the new method, revealed about the same level of mutual linkage between economic and ecological factors and the integral indicator, that positively confirming the validity of competitive comparisons’ mechanism used in this study. If at the macroeconomic level studies a central role was played by the environmental transformation index, reflecting the relative equivalent of not only the natural resources availability, but also of environmental condition as a result of environmental protection measures, as well as the effects of improving the natural environment for other areas of social and economic national-level systems; at the regional scale we are considering research emphasis in the environmental factors integration as to some extent offset to the environmental competitive advantages, associated mainly with regions’ natural resources available. Trends in the microeconomic level: on the background of systematic enough assessment of mutual influence between environmental factors and the macro and meso level economic systems competitiveness formation, namely such concentrated valid arguments regarding micro-level economic systems (products and manufacturers) are still missing. But even some episodic evaluations backgrounded with the results of analytic studies affected by the Sumy State University and the Ukraine NAS Institute of Industrial Economics, do confirm a relatively stable trend in the revealed interdependencies between goods & producers competitiveness and environmental factors. Illustration of this trend is clearly followed in the enterprise potential competitiveness calculation, taking into account environmental factors, we expose herein departs from the study by T.V. Bondar. Conclusions and directions of further researches. In the article we suggest an evaluation of the environmental factor’s influence onto the economic systems’ competitiveness formation. The author shows the presence of sufficiently clearly defined stable trends of interdependence between the economic systems condition existing indicators and their competitiveness at all hierarchical levels of economic systems: macro- (state), mesoeconomic (regions) and the micro (enterprise)one.